Low Irradiation Dose for Sorghum Seed Sterilization: Hydroponic Fodder System and In Vitro Study - Teguh Wahyono; Shintia Nugrahini Wahyu Hardani; Irawans Sugoro (Buletin Peternakan, 2018)
The purpose of this study was to to evaluate the influence of low gamma irradiation dose on growth performance, in vitro gas production and rumen fermentation product of sorghum hydroponic fodder (SHF) to utilize them in ruminant diets. Three polyethylene packages of Samurai 2 sorghum seeds were exposed at 25oC gamma irradiation in gamma cell (Co-60) at doses of 100, 200 and 300 Gy in the presence of air. Samples were then referigated (< 5oC) before planting. All seeds were planted in nutrient film technique hydroponic system. This study used Completely Randomized Design with four replications The observed parameters were total fresh yield, plant height and coversion ratio from seeds to SHF. In vitro gas test evaluation was done to compare all treatments with sorghum straw. The observed parameters were total gas production, kinetics gas, CH4 concentration, CO2 concentration and rumen fermentation products. Results showed that lower irradiation dose for seeds sterilization decreased plant height and total fresh yield on SHF production. In vitro total gas production of all SHF treatment was higher (p<0.05) than sorghum straw (control) at 2-48 h time of incubation. Gamma irradiation dose of 200 and 300 Gy on SHF seeds sterilization decreased (p<0.05) in vitro CH4 concentration for 19.51 and 15.43% respectively compared to SHF control (hypochlorite sterilization). In the same dose, seeds sterilization with gamma irradiation increased (p<0.05) CO2:CH4 ratio by 23.46 and 20.73% respectively compared to SHF control. The treatment of 100 Gy gamma irradiation for seed sterilization also increased (p<0.05) TVFA by 30.63% compared to sorghum straw. It was concluded that lower irradiation dose for seeds sterilization decreased growth performance of SHF. However, 100 Gy gamma irradiation increased in vitro total gas production.